Neurological events and unanticipated risks after locoregional anesthesia (NEURAL): Protocol for a multicenter prospective observational study - Alessandro De Cassai; Elena Ioppolo; Dario Bugada; Francesco Tasso; Gianluca Cappelleri; Vito Torrano (PLoS ONE, 2026)
Background Regional anesthesia is widely regarded as one of the safest anesthetic techniques, yet serious complications—such as nerve injury, hematoma, pneumothorax, and local anesthetic systemic toxicity (LAST)—continue to be reported. Their true incidence remains uncertain, as available data are often derived from registry or retrospective studies with heterogeneous definitions and limited sample sizes. Moreover, the mechanisms underlying complications such as nerve injury are incompletely understood and may extend beyond direct mechanical trauma to include factors such as sub-perineural injection, hematoma formation, altered coagulation, and patient-specific vulnerability. Methods The NEURAL study, promoted by the Italian Society of Anesthesia, Analgesia and Critical Care (SIAARTI), is a multicenter, prospective, observational study designed to determine the incidence and risk factors for complications following single-shot regional anesthesia of the upper limb, lower limb, and fascial plane. The primary endpoint is the composite incidence of nerve injury, hematoma, pneumothorax, and LAST. Secondary objectives include determining the individual incidence of each complication and identifying patient- and procedure-related risk factors. Data will be collected via the REDCap® (Research Electronic Data Capture) platform from more than 40 Italian centers. Standardized follow-up will be performed at 24 and 48 hours, 15 and 30 days, and monthly thereafter for unresolved neurological deficits, up to one year. Statistical analyses will include logistic regression modeling to identify independent predictors of complications. Expected results Based on an estimated complication rate of 0.5%, a minimum of 3,396 patients will be required to ensure adequate precision of incidence estimates. Nationwide participation is expected to exceed this target. Conclusions The NEURAL study will provide robust, prospective, and standardized data on complications of regional anesthesia. By identifying their true incidence and modifiable risk factors, the findings are expected to inform safer clinical practice, enhance patient counseling, and support the development of updated evidence-based guidelines.